A multivariate analysis on prognostic factors for lobular carcinoma of the breast - Köhler, Hugo Fontan; Maciel, Maria do Socorro; Collins, Juan Donoso; Rozenowicz, Renato de Lima; Mourão Netto, Mário (São Paulo Medical Journal, 2010)
CONTEXT AND OBJECTIVE: Lobular carcinoma is the second most common type of breast neoplasia and has unique clinical and pathological features. Our aim was to evaluate prognostic factors for this type of breast cancer. DESIGN AND SETTING: Retrospective study at a tertiary oncological institution. METHODS: 162 patients diagnosed and treated between January 1985 and January 2002 were included. The inclusion criteria were: absence of previous treatment, histological diagnosis of lobular carcinoma, no previous history of breast cancer and minimum follow-up of 36 months. RESULTS: In univariate analysis, the following factors were statistically significant: clinical stage T (P = 0.0005), clinical stage N (P = 0.0014), neoadjuvant chemotherapy (P = 0.0008), primary tumor size (P < 0.0001), vascular invasion (P < 0.0001), lymphatic invasion (P = 0.0004), neural invasion (P = 0.0004), skin invasion (P < 0.0001), capsular transposition (P = 0.0008), lymph node ratio (P < 0.0001), estrogen receptor expression (P = 0.0186), progesterone receptor expression (P = 0.0286), pathological stage T (P < 0.0001), pathological stage N (P < 0.0001), adjuvant chemotherapy (P < 0.0001) and postoperative hormone therapy (P = 0.0367). After grouping the variables, multivariate analysis was performed. Presence of lymph node metastases, capsular transposition, lymph node ratio and postoperative hormone therapy remained significant. CONCLUSION: In this series, the most important prognostic factors for lobular carcinoma of the breast seemed to relate to lymph node status and presence of capsular transposition. Factors relating to axillary involvement, capsular transposition and hormone therapy were significant for survival.